Free radical scavenging potential and HPTLC analysis of Indigofera tinctoria linn (Fabaceae) - Sakthivel Srinivasan; Wankupar Wankhar; Sheeladevi Rathinasamy; Ravindran Rajan (Elsevier, 2016)
The objective of this study was to evaluate the free radical scavenging potential and high performance thin layer chromatography (HPTLC) fingerprinting of Indigofera tinctoria (I. tinctoria). Phytochemical analysis was carried out using standard methods, and free radical scavenging activity of the plant was determined using 2,2-diphenyl-1-picrylhydrazy (DPPH), nitric oxide (NO) and superoxide anion (O2−) radical scavenging capacities. HPTLC plate was kept in CAMAG TLC Scanner 3 and the Rf values at fingerprint data were recorded by WINCATS software. Aqueous extract of I. tinctoria reliably showed the total phenolics (267.2±2.42 mg/g), flavonoids (75.43±3.36 mg/g) and antioxidants (349.11±8.04 mg/g). The extract was found to have DPPH (52.08%), NO (23.12%) and O2− (26.79%) scavenging activities at the concentration of 250 μg/mL and the results were statistically significant compared with ascorbic acid standard (p<0.05). HPTLC results confirmed that the extract contained several potential active components such as phenols, flavonoids, saponins and terpenoids as the slides revealed multi-colored bands of varying intensities. This study confirmed that the plant had multipotential antioxidant and free radicals scavenging activities.